Akuaponik sebagai Sistem Pemanfaatan Limbah Budidaya Ikan Lele di Desa Kalijaran - Murni Handayani; Cahya Vikasari; Oto Prasadi (Jurnal Teknologi dan Rekayasa Manufaktur, 2020)
Fish farming group Mina Jaya Kalijaran village has potential in producing vegetables in the use of aquaponic system, this is because it is supported by abundant waste catfish cultivation. Utilization of catfish cultivation waste is still not maximized. Utilization of catfish cultivation by most members of fish farming group Mina Jaya Kalijaran village still has not led to produce agricultural products in the form of vegetables with aquaponic system. The aim of the empowerment activities of fish farming group Mina Jaya Kalijaran village is to provide knowledge, training and mentoring in utilizing the waste of catfish cultivation using the aquaculture system to produce agricultural products in the form of vegetables and reducing environmental pollution by the catfish cultivation waste. The activity received positive response from fish farming group of Mina Jaya Kalijaran village. The result of this empowerment activities is fish farming group Mina Jaya Kalijaran village become an undestand an able to make installation of aquaponic system by utilizing waste catfish farming to get additional results namely agricultural products in the form of and can reducing environmental pollution.